Experiences with Coding using ICD-11: "The Codes Paint a Clearer Picture". (2018) - Eastwood, Catherine; Southern, Danielle; Boxill, Alicia; Maciszewski, Malgorzata; Quan, Hude; Cullen, Denise; Penchoff, Margaret; Ghali, William
No abstract available